Development and assessment of a pictorial guide to improve accuracy of visual estimation of blood loss of small animals. (May 2020) - Cumming, Scott H.; Martinez-Taboada, Fernando
Abstract: Objective: To investigate the accuracy of visual blood loss estimation from small animals among veterinary staff and final-year veterinary students, and the development and utility of a pictorial guide to improve estimation, in a veterinary hospital. Study design: Online anonymous voluntary survey. Methods: A two-part online survey was circulated to voluntary participants at the University Veterinary Teaching Hospital Sydney, The University of Sydney, including students, nurses, interns, residents, general practitioners and specialists. The survey consisted of visual and brief descriptive depictions of blood loss scenarios involving small animals, principally including images of common surgical items and receptacles containing a bloodlike substance. Each participant estimated the blood volume (in millilitres) for each scenario two times, initially [Pre-Guide (PGD)] and then with the aid of a pictorial guide [With-Guide (WGD)]. The pictorial guide used similar images labelled with corresponding volumes. Data were analysed for normality with the Shapiro–Wilk test, corrected to absolute error and compared for statistical significance using the Wilcoxon signed-rank test or the Kruskal–Wallis test as appropriate ( p < 0.05). Results: A total of 59 participants provided 288 responses. The raw median PGD error was –16 mL (range –105 to 443 mL), indicating a tendency towards underestimation of the actual volume. The WGD median error was 18 mL (range –91 to 191 mL), indicating a tendency towards overestimation when using a pictorial guide ( p < 0.0001). Data corrected to absolute error showed a PGD median error of 34 mL (range 0–443 mL) and WGD median error of 23 mL (range 0–191 mL; p < 0.0001). There were differences between the participant roles in the PGD phase but not when using the pictorial guide. Conclusions: and clinical relevance Participants generally underestimated surgical blood loss, with a wide variation, when visually estimating scenarios involving small animals. A pictorial guide improved estimation by reducing the absolute median error and narrowing the range.